2011
DOI: 10.1007/bf03346715
|View full text |Cite
|
Sign up to set email alerts
|

Mini-invasive video-assisted surgery of the thyroid and parathyroid glands: A 2011 update

Abstract: Thyroid surgery during the last century was characterized by a development of Kocher's concepts: through a relentless work of surgeons from all over the world thyroidectomy reached a standard of quality in terms of overall results which was unimaginable in the first half of the XX century. The flattering data collected in the literature until the 90's were all concordant in assuming that there would be little space for a real improvement in the quality standard of thyroid surgery. The introduction of laparosco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
20
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(26 citation statements)
references
References 75 publications
5
20
0
1
Order By: Relevance
“…The literature seems consistent with a better postoperative outcome of MIVAT (17). In particular, during the whole postoperative period, it has been found that patients take less pain medications.…”
supporting
confidence: 71%
See 2 more Smart Citations
“…The literature seems consistent with a better postoperative outcome of MIVAT (17). In particular, during the whole postoperative period, it has been found that patients take less pain medications.…”
supporting
confidence: 71%
“…Recently, Miccoli et al (17) showed that the rate of complications involving the RLN is substantially similar to that already described in the literature; however, the study indicates that in tertiary referral centers, the incidence may prove slightly higher because of the large number of patients who undergo MIVAT, and of the frequently malignant nature of the underlying disease. Paradoxically, the use of advanced surgical instruments might further increase such rate, for instance due to heat transmission caused by the ultrasound scalpel that some surgeons use for coagulating and dividing vessels.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…However, the appearance of minimally invasive techniques for head and neck conditions opened a new possibility of treatment for thyroid cancer. The first attempt was the minimally invasive video-assisted thyroidectomy designed by Miccoli et al [22]. Soon, other surgical techniques as breast-access minimally invasive thyroidectomy [23], axillary robotic-assisted thyroidectomy [24] and face-lift robotic assisted thyroidectomy [25] has also been suggested as minimally invasive.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, the imaging tests, the treatment, and the intraoperative control arrangements are still being debated. There are two different surgical strategies: Exploratory cervicotomy with visualisation of the four glands or focused minimally invasive surgical approach 2,3 enabling the visualization of one or two glands. However, the lack of visualization of the four glands makes it impossible to rule out multiglandular involvement and, in particular, the rare case of double adenomas, and because of that, some authors recommend systematic intraoperative PTH assays (intraoperative assay of the PTH or tissue PTH).…”
Section: Introductionmentioning
confidence: 99%